Peran Stres terhadap Emotional Eating pada Mahasiswa: Penelitian - Rafiq Tri Belan Harjuna; Hasnida; Rahma Fauzia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the role of stress on emotional eating behavior in college students. College students often experience high levels of academic, emotional, and social pressure, especially those who live away from home. Emotional eating, the tendency to eat in response to negative emotions rather than physical hunger, is a common response to stress. This study used a quantitative approach with a correlational design and involved 200 respondents selected through accidental sampling. Data were collected using the Perceived Stress Scale (PSS) and the Dutch Eating Behavior Questionnaire (DEBQ), then analyzed using linear regression. The results showed that stress played a significant role in emotional eating (p < 0.05), with a contribution of 8%. This means that the higher the stress level, the greater the tendency for students to experience emotional eating.